The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.5539/ijc.v5n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth and Structure of a New PbHNSO3 Crystal

Abstract: A new type of PbHNSO 3 crystal has been grown by a gel method using agar-agar gel. TG-DTA and X-ray diffraction measurements have been performed on single crystal samples of PbHNSO 3 . It is found that the thermal decomposition of the compound starts at about 960 K. The space group (orthorhombic Pnma) and structural parameters are determined at room temperature with unit cell dimensions: a=8.4690(6), b=5.3934(4) and c=6.9530(4) Å. The crystal structure is found to consist of NSO 3 pseudo-tetrahedra, PbO 9 N 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…30,32,36,40,48 Surprisingly, to the best of our knowledge, no second-harmonic generation measurement has been published on any metal amidosulphate compound as yet. Several studies on the thermal decomposition of metal amidosulphates suggested a quite complex decomposition pattern, 22,47,52 in parts involving condensation reactions to imidodisulphates, which is a first indication that such species might be suitable precursors to sulphur nitrides.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…30,32,36,40,48 Surprisingly, to the best of our knowledge, no second-harmonic generation measurement has been published on any metal amidosulphate compound as yet. Several studies on the thermal decomposition of metal amidosulphates suggested a quite complex decomposition pattern, 22,47,52 in parts involving condensation reactions to imidodisulphates, which is a first indication that such species might be suitable precursors to sulphur nitrides.…”
Section: Introductionmentioning
confidence: 98%
“…Though dibasic imidosulphate [NHSO 3 ] 2− anions 22,23 and tribasic nitridosulphate [NSO 3 ] 3− anions [24][25][26] have been occasionally encountered, most of the studies on the crystal structures of the metal salts of amidosulphuric acid feature monobasic amidosulphate [NH 2 SO 3 ] − anions. For monovalent ions, besides the double salts MLi(NH 2 SO 3 ) 2 (M = K, Rb, and Cs), 27 amidosulphates of the alkali metal ions Li + to Cs + , [28][29][30][31][32][33][34][35][36][37] the pseudo-alkali cations ammonium, Ag + and Tl + have been structurally characterised.…”
Section: Introductionmentioning
confidence: 99%